ARTICULAÇÃO DO TRABALHO PEDAGÓGICO DO ATENDIMENTO EDUCACIONAL ESPECIALIZADO COM O ENSINO REGULAR NA REDE MUNICIPAL DE CORUMBÁ (MS) - KARINY ARAUJO DELGADO TROVO (2023)
The Education from the perspective of inclusive education is a topic of great relevance today, mainly because it provides important discussions and reflections for the construction of an inclusive society, which should value diversity and human dignity. In this perspective, inclu-sive education aims to ensure that all people have access to quality education, regardless of their physical, sensory and intellectual conditions. The Multifunctional Resource Room (SRM) is a very important space within an inclusive school , which aims at specialized educational care to students with special educational needs , whose service should serve as support to the target public students of special education, having the role of facilitator in access to knowledge. In this context, this study aims to understand how the articulation of the pedagog-ical work of the Specialized Educational Service occurs with the pedagogical work of the teachers of the regular education of the students in the municipal network of Corumbá (MS). Through a qualitative research, the investigation is based on the reports of the interviews of seven teachers of the Specialized Educational Service (AEE) and seven regent teachers of the regular room of the municipal network of Corumbá (MS), who work in Elementary School I, in which they attend Special Education students attended by the AEE. For the analysis of the material was divided into three main axes: forms of articulation between the work of the teachers, impediments raised for the non-occurrence of the articulations between the teachers and the vision of the role of the Specialized Educational service by both teachers, with the interlocutions of the literature produced on the subject by researchers such as: Kassar, Rebelo, Camargo, Bueno, Pletsch, among others. As a result, it was verified that there is no systema-tization that favors the articulation between the work of the teacher of the Specialized Educa-tional Service and the regent teacher of the target public students of special education, the discontinuity of educational policies that also harm the work in the education network, be-cause the collaborative work demands time and relationship of trust. The data also showed that both teachers identify the need for innovative practices to favor the learning of the PAEE student, however, not all of them can still generalize the application of these practices to the entire classroom in order to benefit all students, not only the student with disabilities. We conclude that collaborative planning, constant and systematized communication, continuing education, use of technological resources and joint evaluation between SRM and regular edu-cation teachers are fundamental to promote student learning. The articulation between cross-functional resource room teachers and regent teachers can be a complex and challenging is-sue, but it is essential to ensure an inclusive and quality education for all students.